Acne vulgaris in a 22‐year‐old cystic fibrosis patient treated with Elexacaftor‐Tezacaftor‐Ivacaftor and good clinical response to isotretinoin-A case report - Isabelle Pfeiffer; Mark Berneburg; Zeljka Hopfner; Dennis Niebel (Wiley, 2024)
Abstract Cystic fibrosis (CF) is a rare autosomal recessive genetic disorder that is now commonly treated with cystic fibrosis transmembrane conductance regulator (CFTR) modulators. Typical adverse events comprise new onset (drug‐induced) acneiform eruption as well as worsening of pre‐existing acne vulgaris. We present a case report of a young adult with rapid CFTR‐modulator‐induced worsening of pre‐existing acne vulgaris refractory to minocycline treatment, which resolved within 8 months of low dose isotretinoin therapy. Monthly laboratory monitoring of liver function, lipid levels and blood count were unremarkable in this case. The optimal treatment of acne vulgaris in CF‐patients and the management of drug‐induced acne remain a challenge. The latter may jeopardize drug adherence. CFTR‐modulators might be capable to induce acneiform skin lesions by altering electrolyte concentrations and sweat production with subsequential changes of the microbiome and follicular inflammatory response. The exact mechanism remains elusive at this point and warrants further investigation.